Transforming provisioning systems to enable 1.5° lifestyles in Europe? Expert and stakeholder views on overcoming structural barriers - Halliki Kreinin; Doris Fuchs; Pia Mamut; Steffen Hirth; Steffen Lange (Sustainability: Science, Practice, & Policy)
This article explores the urgent need for transformative change toward provisioning systems that align with staying as close as possible to the Paris Agreement’s 1.5 °C limit for climate change. Despite historical awareness of the need for change, current unsustainable patterns of production and consumption persist, prompting an examination of the role of societal structures in hindering transformative change. Using the framework of provisioning systems, this study analyses expert and stakeholder views on structural barriers and steps to overcome them. Based on 36 expert interviews and Stakeholder Thinking Labs with 113 participants in five European Union case countries, the study identifies and discusses seven key structural barriers that affect the sustainability of provisioning systems for food, mobility, housing, and leisure. These barriers include the economic growth paradigm, policy incoherence, vested interests, the externalization of environmental costs, dominant narratives of the good life, inequality, and an insufficient integration of environmental concerns in educational systems. When considering the actualization of these structures in concrete provisioning systems, stakeholders emphasize the need for welfare provision with improved resource efficiency; argue for radical measures such as bans, limits, and taxes to address these challenges; and highlight governance challenges related to participation and power. The analysis underlines the complexity of promoting transformative structural change and the interplay of structures in different provisioning systems, emphasizing the need for a holistic approach to achieve sustainable provisioning systems and 1.5° lifestyles.